Pengaruh Kualitas Pelayanan Dan Harga Tiket Terhadap Kepuasan Penumpang Maskapai Batik Air Di Bandar Udara Abdulrachman Saleh Malang - Maulana Fadli; Desiana Rachmawati (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Passenger satisfaction is a very important thing for an airline to be one of the benchmarks to see how far the company's success is in carrying out its vision and mission. The purpose of this study was to determine partially significant Customer Service Quality towards Batik Air Airline Passenger Satisfaction at Abdulrachman Saleh Airport Malang. To find out ticket prices partially significant to Batik Air Airline Passenger Satisfaction at Abdulrachman Saleh Airport Malang. To determine the effect of Customer Service Quality and Ticket Prices simultaneously on Batik Air Airline Passenger Satisfaction at Abdulrachman Saleh Airport Malang. This research uses descriptive quantitative methods. And multiple linear analysis technique. The number of samples used is 100 respondents. Data collection techniques in this study using a questionnaire. Data processing in this study uses the SPSS software program. The conclusion of this study can be seen that the Quality of Customer Service has a positive and significant influence on Passenger Satisfaction, Ticket Prices have a positive and significant influence on Passenger Satisfaction. Simultaneously it is known that the Quality of Customer Service and Ticket Prices have a positive and significant influence on Batik Air Airline Passenger Satisfaction at Abdulrachman Saleh Airport Malang.